Design of Experiments Analysis of Friction Behavior of Al-TiB2 Composite. (2017) - Poria, S.; Sutradhar, G.; Sahoo, P.
Abstract: The present study considers the friction behaviour of aluminium matrix composites reinforced with TiB2 micro particles. Different weight percentages of micro-TiB2 powders with average sizes of 5-40 micron are incorporated into molten LM4 aluminium matrix by stir casting method. The coefficient of friction of Al-TiB2 composites is evaluated in a block-on-roller type Multitribo tester at room temperature. Taguchi L27 orthogonal array is used as design of experiment. A second order regression analysis is done. Taguchi method is implemented to find out the optimal combination of parameters. Analysis of variance (ANOVA) is used to find out the percentage of contribution of each parameter on coefficient of friction. Weight percentage of TiB2 is forced to be the most effective parameter in controlling coefficient of friction.